2017
DOI: 10.1111/jicd.12283
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical analysis of collagen reorganization at the invasive front of oral squamous cell carcinoma tumors

Abstract: Collagen has natural birefringence, which is attributed to the arrangement of its fibers, and is enhanced by staining, such like Van

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…During malignant transformation, elongated projection of the core of the papilla from the LP into the tumor has been noted in histology, which presents highly retardant spikes seen in cross-sectional, cumulative PS-OCT ( Figure 3 B,G). These retardant changes in PS-OCT are consistent with previous studies using Picrosirius red staining and polarized light microscopy, which have shown densely packed collagen fibers with high birefringence surrounded the tumor islands in well-differentiated tumors [ 18 , 19 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…During malignant transformation, elongated projection of the core of the papilla from the LP into the tumor has been noted in histology, which presents highly retardant spikes seen in cross-sectional, cumulative PS-OCT ( Figure 3 B,G). These retardant changes in PS-OCT are consistent with previous studies using Picrosirius red staining and polarized light microscopy, which have shown densely packed collagen fibers with high birefringence surrounded the tumor islands in well-differentiated tumors [ 18 , 19 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 91%
“…The morphological change of stroma can be easily seen in conventional histology, like the change of core of papilla [ 17 ]. The changes in collagen fiber’s diameter, orientation, density, and packing during malignant transformation have also been studied in polarized light microscopy with Picrosirius red stain [ 18 , 19 ]. However, most of these studies are ex vivo and cannot be translated into clinical diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Progression to malignancy is primarily related to two components – the action of malignant epithelial cells and the reaction of the stroma (extracellular matrix) of the oral mucosa [3]. Whereas the epithelial component of OSCC has been the subject of many studies, the role of the extracellular matrix has more recently captured researchers’ attention [4–8]. Most studies have investigated stromal changes ex vivo , in particular, in collagen fiber organization (i.e., arrangement and density) by polarized light microscopy using Picrosirius red staining (PSR-POL) [4–9].…”
Section: Motivationmentioning
confidence: 99%
“…Whereas PSR-POL is an established method for visualizing collagen fibers in histopathological sections, due to its low cost and availability in most clinical laboratories, second harmonic generation (SHG) microscopy is the gold standard for assessing collagen properties in experimental research settings, because of its high resolution and nondestructive imaging of both stained and unstained tissues up to 200 µm thick, many times the thickness of standard 5-µm pathology sections. However, the link between reduced collagen organization and oral tumor progression has primarily been investigated by means of PSR-POL [4–8] and only occasionally by SHG microscopy [10,11]. PSR-POL has shown that the oral stroma undergoes a change in birefringence, because of altered arrangement and density of its collagen fibrils, predominantly caused by tumor invasion [8].…”
Section: Motivationmentioning
confidence: 99%
“…Regarding pathological tissues, we could not compare our estimated sizing data with real data from the literature, but as indicated by some authors, [49][50][51] when cancer invades mucosal stroma, collagen fibrils increase in the length, diameter, and density. This means that the estimations we made with Eq.…”
Section: Data Estimation For Natural Tissuementioning
confidence: 91%